2011
DOI: 10.1375/brim.12.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Intervention in a Case of Korsakoff's Amnesia

Abstract: T he cognitive symptoms that characterise the Wernicke-Korsakoff's syndrome include anterograde amnesia, confabulation, temporal-spatial disorientation, severe apathy, poor awareness of one's own mental state and changes in executive functions. Such deficits may persist even after the clinical profile stabilises. There are no studies that report an intervention after the acute phase, possibly due to the complexity of these cases. This study provides a descriptive analysis of neuropsychological rehabilitation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Memory aids and environmental modifications should also be used in the rehabilitation of ARBD, as they can improve daily functioning and may reduce the anxiety and social embarrassment associated with memory impairment (Davies & Binks, 1983;Lenanne, 1986;Morgan et al, 1990;Monteiro et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Memory aids and environmental modifications should also be used in the rehabilitation of ARBD, as they can improve daily functioning and may reduce the anxiety and social embarrassment associated with memory impairment (Davies & Binks, 1983;Lenanne, 1986;Morgan et al, 1990;Monteiro et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the findings from this review indicate that a variety of psychosocial interventions are beneficial in the rehabilitation of ARBD. It is therefore recommended that practitioners should deliver structured group and individual psychosocial interventions which focus on establishing regular daily routines, such as self-care habits, regular meal times and participation in timetabled activities, within an alcohol-free environment (Lenanne, 1986;Monteiro et al, 2011;Wilson et al, 2012). Many individuals with ARBD may be socially isolated (MacRae & Cox, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, only two case reports have addressed this issue (Monteiro et al, 2011 ; Genç et al, 2018 ), but none of them covered long-term follow-ups. In detail, one case study of a 48 year WKS patient with a history of heavy drinking, reported outcomes of inpatient neurorehabilitation (Genç et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%